2020
DOI: 10.3390/nu12020398
|View full text |Cite
|
Sign up to set email alerts
|

Impending Low Intake Dehydration at Admission to A Geriatric Ward- Prevalence and Correlates in a Cross-Sectional Study

Abstract: Dehydration risk increases with frailty and functional dependency, but a limited number of studies have evaluated this association in hospitalized geriatric patients. This cross-sectional study aimed to assess the prevalence and determinants of dehydration in patients admitted to the geriatric ward. Dehydration was diagnosed when calculated osmolarity was above 295 mMol/L. Logistic regression analyses (direct and stepwise backward) were used to assess determinants of impending dehydration. 358 of 416 hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
12
2
Order By: Relevance
“…Given the well documented relation between kidney disease and hydration, 22 we further tested the association between sodium excretion and hydration status excluding participants with self‐reported renal disease ( n = 123).…”
Section: Methodsmentioning
confidence: 99%
“…Given the well documented relation between kidney disease and hydration, 22 we further tested the association between sodium excretion and hydration status excluding participants with self‐reported renal disease ( n = 123).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, increasing TWI is important for elderly adults who live in geriatric facilities, because dehydration is associated with significant adverse outcomes in older people despite being largely preventable and treatable [121]. For example, two recent European studies published in Nutrients reported that dehydration (P OSM > 295 mOsm•kg −1 ) was observed in 58.4% of 358 individuals (86% > 75 y) [122] and that a S Na+ value ≥ 140 mMol•L −1 could be used as a first-step screening procedure for detecting underhydration in geriatric patients [99]. Similar to LOW, older adults can be encouraged to increase TWI by building upon existing habitual drinking patterns [121].…”
Section: Select Solid Foods With a High Water Contentmentioning
confidence: 99%
“…A recent study by Wojszel [ 12 ] also chose to use calculated osmolarity (see Table 1 ) and assessed the correlation between this measure and different patient characteristics. In 209 (58%) patients impending dehydration (>295 mmol/L) was detected at admission to the geriatric department.…”
Section: Resultsmentioning
confidence: 99%
“…In 209 (58%) patients impending dehydration (>295 mmol/L) was detected at admission to the geriatric department. Impeding dehydration was more frequent in patients with multimorbidity, different chronic diseases and polypharmacy [ 12 ], which are well-known risk factors for low-intake dehydration assessed by measured serum osmolality and described in the ESPEN guideline [ 4 ].…”
Section: Resultsmentioning
confidence: 99%